Predicting heating values of lignocellulosics and carbonaceous materials from proximate analysis - Cordero, T.; Marquez, F.; Rodriguez-Mirasol, J.; Rodriguez, J. J. (Fuel, 2001)
A simple equation based on proxymate analysis (volatile matter and fixed carbon contents) is presented which allows calculation of the higher heating value of lignocellulosic as well as the charcoals resulting from their carbonization. The equation has been tested with different lignocellulosic wastes and chars obtained from carbobization at different temperatures. Derivations from the experimental heating values fall in most cases below 2%. A comparison is presented with some equationsfrom the literature based on proximate, ultimate and chemical analysis data. As a general conclusion the equation proposed in this paper leads to comparableand in many cases more accurate predictions of heating valus and has the advantage of being applicable to a wide range of carbonaceous materials, requiring only a simple, rapid and cheap proximate analysis of the samples
Keywords: charcoal; heating value calculation; lignocellulosics